PENGARUH LINGKUNGAN TERHADAP KELENTURAN FENOTIPIK (phenotypic plasticity) TERNAK - Hoda, Abdurahman (Green Earth, 2012)
Protection and development of local-breed breed is very important because it can utilize low-quality feed and are more resistant to environmental stress and disease. It is very important also for the development and utilization of local breeds because they are very well adapted to their environment, with a very limited nature and management are very low. The method used was literature study, which is to identify how the environmental effects toward the phenotypic Plasticity livestock.The results of research showed that the phenotypic and genotypic expression is caused by environmental factors such as pathogen infection or a biotic factors (light, temperature, oxygen, drought, nutrients) as well as the use of biotechnology through genetic engineering (gene recombination), gene expression conducted in two stages,transcription and translation. Protein synthesis mechanisms controlling gene regulated by the regulator (regulator gene), gene operator (operator gene), and gene structure (structural gene). On one way to regulate the effectiveness of the enzyme byÂ genetic control, development of farm businesses in areas that have problems due to a less than optimal environment, it can develop local cattle.Â Keywords: environment, phenotypic plasticity, livestock.